Differences inquiry learning model and problem based learning model on cognitive learning outcomes and critical thinking of students Class VII SMP in Ambon concepts environmental pollution - Nathalia Jessy Gomies; Johanis Fritzgal Rehena; Sintje Liline (Program Studi Pendidikan Biologi, Pascasarjana, Universitas Pattimura, 2023)
This study aims to look at the differences between Inquiry learning model and Problem Based Learning model on cognitive learning outcomes and critical thinking of class VII students of SMP in Ambon City concepts environmental pollution. This research was conducted at SMP Negeri 4 Ambon, SMP Negeri 20 Ambon and SMP Negeri 22 Ambon. The analysis technique used in this research is descriptive statistics and inferential statistics. The results showed that the mastery of biological concepts before the learning model was applied was very low. This can be seen in the students pre-test with an average score of < 70. After applying the learning model, the results show that there is an influence of the Inquiry learning model and the Problem Based Learning (PBL) learning model on cognitive learning outcomes and critical thinking.